THE EFFECT OF BODY CHECKING POLICY CHANGE ON OFFENSIVE GAME SKILL PERFORMANCE IN 13–14 YEAR OLD ICE HOCKEY PLAYERS. Issue 4 (1st February 2017) - Kolstad, Ash; Nadeau, Luc; Eliason, Paul; Palacios-Derflingher, Luz; Goulet, Claude; Emery, Carolyn A.
Abstract : Background: Policy allowing body checking (BC) increases injury and concussion risk in youth ice hockey players. Hockey Calgary introduced BC policy change in 2015 that disallows BC at the Bantam (ages 13–14) non-elite level (lowest 60% by division of play). Objective: To compare game offensive performance (OP) between non-elite Bantam players playing in a league allowing BC and players in a league not allowing BC. Design: Prospective cohort. Setting: Arenas in Calgary, Alberta. Participants: Non-elite Bantam games were videotaped in Calgary, Alberta during the 2014–15 (n=348 players) and 2015–16 (n=309 players) playing seasons. Assessment of Risk Factors: Players from the 2014–15 season played in a league allowing BC, while players from 2015–16 season played in a league where BC was not allowed. Main Outcome Measurements: Using Dartfish video analysis software, games were analyzed for OP metrics for the puck carrier using the ice hockey adapted Team Sport Assessment Procedure. These metrics included puck possession (conquered puck from an opponent and received pass from a teammate) and puck outcome (successful shot on goal, lost puck to an opponent, and offensive pass to a teammate). Unadjusted incidence rate-ratios (IRRs), clustered by game, were calculated for each puck action per team game between players in Calgary, Alberta 2014–15 (BC allowed) and 2015–16 (BC not allowed). Results: No differences were found in puck possession metrics [conquered puck IRR=1.07 (95% CI: 1.00, 1.16), received pass IRR=1.05 (95% CI: 0.93, 1.18)] or puck outcome [successful shot IRR=0.97 (95% CI: 0.86, 1.10), lost puck IRR=1.07 (95% CI: 0.98, 1.18), offensive pass IRR=0.98 (95% CI: 0.86, 1.12)]. Conclusions: There were no differences found across all OP metrics between a non-elite Bantam league allowing BC and a league not allowing BC. There is no evidence to conclude that offensive performance was negatively nor positively affected by Hockey Calgary's decision to disallow BC at Bantam non-elite levels.